Le Henri VIII de Saint-Saëns : entre affirmation idéologique et liberté théâtrale - Thierry Santurenne (Revue LISA)
A late example of French grand opera, Saint-Saëns’ Henri VIII (1883), a setting of the libretto by Léonce Détroyat and Armand Silvestre draws from Shakespeare’s and Fletcher’s Henry VIII as well as Calderón de la Bark’s La Cisma de Inglaterra. Composed and first performed when the French Republic was trying to assert itself through its policy of separating church and state policy, the opera reflected the contemporary debate on divorce. Yet, the ideological purpose of the libretto is nuanced by the composer’s reliance on specific musical and dramatic formulas.